The international transmission of monetary policy - Claudia M. Buch; Matthieu Bussiere; Linda Goldberg; Robert Hills (Deutsche Bundesbank, 2018)
This paper presents the novel results from an internationally coordinated project by the International Banking Research Network (IBRN) on the cross-border transmission of conventional and unconventional monetary policy through banks. Teams from seventeen countries use confidential micro-banking data for the years 2000 through 2015 to explore the international transmission of monetary policies of the U.S., euro area, Japan, and United Kingdom. Two other studies use international data with different degrees of granularity. International spillovers into lending to the private sector do occur, especially for U.S. policies, and bank-specific heterogeneity influences the magnitudes of transmission. The effects are supportive of the international bank lending channel and the portfolio channel of monetary policy transmission. They also show that the frictions that banks face matter; in particular, foreign currency funding and hedging considerations can be a key source of heterogeneity. The forms of bank balance sheet heterogeneity that differentiate spillovers across banks are not uniform across countries. International spillovers into lending can be large for some banks, even while the average international spillovers of policies into nonbank lending generally are not large.
Keywords: E52; F3; F4; G15; G21; 330; monetary policy; international spillovers; cross-border transmission; global bank; global financial cycle